Small bowel obstruction: need for surgery based on history and radiology - Meena, L. N.; Bhatt, Neha; Jain, Sanchit (International Surgery Journal, 2018)
Background: Small bowel obstruction is a common clinical challenge because the proper management of small bowel obstruction requires a methodology which on one hand can promptly recognise the presence of strangulation-obstruction and hence the need for urgent operative intervention; and on the other hand, can avoid a non-therapeutic laparotomy along with its associated morbidities and further adhesion formation with its potential sequelae. The study was done to identify relevant features in the patient’s clinical and CT abdomen findings which when present would be highly predictive of the requirement of an operative intervention in a patient with small bowel obstruction. Methods: The study was a hospital based analytical observational study on patients admitted from March 2013 to May 2014 with a diagnosis of small bowel obstruction and who underwent a concurrent CT abdomen. Correlation of line of management was done with respect to the three chosen parameters, obstipation (history), mesenteric edema (CT imaging) and lack of small bowel feces Sign (CT imaging). Results: A total of 74 patients were included with Male:Female ratio being 3.1:1. Forty patients were managed conservatively and remaining underwent surgery with adhesions being the most frequent etiology. The most common operative procedure performed was adhesiolysis with or without band release. Twenty-three cases were performed by open method and remaining laparoscopically. Evaluation of the three parameters revealed that these variables, when present independently or in combination, are predictive for need for operative intervention (p-value <0.001). The sensitivity and specificity to predict the need for exploration when all 3 features were present concurrently was 38.24% and 100%, respectively. Conclusions: Small-bowel obstruction is a common surgical dilemma, the management of which is dealt on a daily basis by surgeons and non-surgeons. The management using variables based on history and radiology may help classify patients into those requiring conservative management and those in need of early exploration.